Love's labour's lost - Shakespeare, William; David, Richard (London : Methuen, 1968)
The Library of Congress, William Shakespeare's "Love's Labour's Lost," a reading staged by Arnold Moss, presented under the auspices of the Gertrude Clarke Whittall Poetry and Literature Fund, production stage manager, Seymour Milbert, costume superviser Ruth Frank.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1959.